The Effectiveness of Origami to Teach the Pillars of Faith at Tadika Al-Fikh Orchrd Tahfiz Nur Furqan - Cintia, Cintia; Zailani, Zailani (Universitas Pahlawan Tuanku Tambusai, 2025)
Early Childhood Education (PAUD) is a crucial stage in children's cognitive, motoric, and social development. One innovative method in PAUD learning is the use of origami as a teaching tool. This study aims to evaluate the effectiveness of origami in teaching the concept of the Pillars of Faith to early childhood students. Conducted at Tadika Tahfiz Nur Furqan, Kedah, Malaysia, this research employs a qualitative approach with a descriptive method. Data collection techniques include direct classroom observations, in-depth interviews with educators, and document analysis of lesson plans and student activities. The findings indicate that origami enhances children's comprehension of the Pillars of Faith by making abstract concepts more tangible and engaging. It also improves children's fine motor skills, focus, and enthusiasm for learning. The project-based and interactive approach fosters a more dynamic learning experience, leading to better retention and understanding. These results highlight the potential of origami as an effective pedagogical tool in early childhood Islamic education.